The influence of weekly sprint volume and maximal velocity exposures on eccentric hamstring strength in professional football players - Shah, S. (University of Stirling, 2022)
Background: Hamstring strains are the most common injuries of moderate and major severity in football. To reduce the risk of these injuries it is important to understand the mechanisms and risk factors that cause them. Sprinting is the primary cause of hamstring injuries, with eccentric hamstring strength identified as a risk factor. Objective: To identify any relationships between sprinting and eccentric hamstring strength by investigating the influence of total weekly sprint distance (m) and weekly efforts >90% and >95% of an individual`s maximum velocity on the eccentric force output of the hamstring muscles. Methods: Fifty-eight professional male football players were observed over one and a half football seasons. The players` weekly movements and speeds were monitored during training and matches using GPS, while eccentric hamstring strength was measured during the Nordic Hamstring Exercise, on the NordBord, as part of their weekly strength and conditioning session. Results: Weekly sprint distance (p = -0.13, P < 0.01) and weekly efforts >90% of maximum velocity (? = -0.08, P = 0.01) both had significant inverse relationships with percentage change in eccentric hamstring strength, with very small correlations; however, total weekly efforts >95% of maximum velocity showed no relationship (p = -0.02, P = 0.45). Only weekly efforts >90% of maximum velocity significantly influenced the mean percentage change in eccentric hamstring force, F (3, 58) = 3.71, P = 0.01, with significant differences occurring when comparing 7-8 sprint efforts with 0-2 efforts (0.11%, P = 0.03) and 5-6 efforts (0.12%, P = 0.03). Conclusion: Eccentric hamstring strength levels significantly decrease when 7-8 weekly sprint efforts are completed at a maximum velocity >90% but are not significantly influenced by total weekly sprint distance or the weekly number of sprint efforts completed at a maximum velocity >95%.